Perbandingan Maf'ul Mutlaq Bahasa Arab dan Cognate Object Bahasa Inggris serta Analisis Sintaksis Maf'ul Mutlaq pada Juz 'Amma - Muhammad Jundi; Yuslin Kasan; Suleman D. Kadir (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2021)
This article aims to discuss the concept of absolute objects or maf'ul muthlaq in the Arabic perspective and analyze the examples in the Alquran, especially in juz Amma. Besides that, this article is also enriched with a comparative analysis between the concept of maf'ul muthlaq and the concept of cognate objects in English which are considered to have some similarities. In writing this article, the author uses descriptive qualitative approaches and types of library research. Data collected from primary and secondary sources include: articles in scientific journals relating to the study of nahwu and grammar, Arabic language books both in Indonesian as well as Arabic, seminar proceedings, scientific papers and so on. Furthermore, the data is read repeatedly, compared then analyzed to formulate conclusion. The finding shows that there are 15 maf'ul muthlaq case in juz Amma scattered in 8 surahs. 11 of them are maf'ul muthlaq as an affirmation and the remaining 4 are maf'ul muthlaq in qualitative meaning. All of them use fathah grammatical markers. The absolute object or maf'ul muthlaq and cognate object have similarities and differences. The similarities are in terms of the forming verb stem and the meaning of the absolute object itself as an explanatory type. While the differences are in the type of verb that can nominalize as an absolute object itself and its function as an affirmation and explanation of numbers.